2016
DOI: 10.4041/kjod.2016.46.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of digital dental models obtained from dental cone-beam computed tomography scan of alginate impressions

Abstract: ObjectiveTo investigate the dimensional accuracy of digital dental models obtained from the dental cone-beam computed tomography (CBCT) scan of alginate impressions according to the time elapse when the impressions are stored under ambient conditions.MethodsAlginate impressions were obtained from 20 adults using 3 different alginate materials, 2 traditional alginate materials (Alginoplast and Cavex Impressional) and 1 extended-pour alginate material (Cavex ColorChange). The impressions were stored under ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
1
16
1
2
Order By: Relevance
“…More and more imaging devices enabling digital data acquisition from impressions and plaster models have become available [7]. Accordingly, the accuracy of digital models has been assessed in many previous studies [2,10,14,15,20]. Studies have generally evaluated the accuracy of the digital models obtained by scanning plaster models with various devices or compared linear measurements of digital models with the corresponding values of plaster casts [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more imaging devices enabling digital data acquisition from impressions and plaster models have become available [7]. Accordingly, the accuracy of digital models has been assessed in many previous studies [2,10,14,15,20]. Studies have generally evaluated the accuracy of the digital models obtained by scanning plaster models with various devices or compared linear measurements of digital models with the corresponding values of plaster casts [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…This method is advantageous in that an additional machine is not required for digital model generation, the scanning time is relatively short, the patient experiences no discomfort, and the characteristics of the X-ray penetrance prevent information loss regardless of the shape of objects such as undercut, in contrast to direct optical scans of the patient's mouth [11][12][13]. Digital Imaging and Communications in Medicine (DICOM) data that are obtained from CBCT devices can also be converted into STL data using various software [14][15][16]. Thus, the performance of the conversion software also affects the accuracy of the digital models.…”
Section: Introductionmentioning
confidence: 99%
“…However, extendedpour alginate with high volumetric stability can be scanned using CBCT to produce a digital model. 8,9 Although it is generally recommended to perform the CBCT scan immediately after impression tak ing, it can be delayed up to 2 or 3 hours when a highstabil ity impression material is used. 9 This study performed CBCT scans at a resolution of 0.1 mm, which improved the accuracy of the digital mod els relative to those obtained by scanning at resolutions of >0.15 mm to 0.3 mm, as performed in previous stud ies.…”
Section: Discussionmentioning
confidence: 99%
“…8 In previous studies, the dimensional accuracy of dig ital models obtained from CBCT scans of alginate im pressions was examined according to the elapsed time. 8,9 However, no published study has evaluated the dimen sional accuracy of digital models obtained using CBCT. Therefore, there is a lack of studies investigating the ac curacy of digital models produced using CBCT, and the width of individual teeth and the entire arch obtained us ing a digital model must be validated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that (Hydrogum 5) extended-pour alginate impressions show promising dimensional stable up to 120 hours at consistent temperature and humidity (20,25) . However, other study has shown that Hydrogum 5, was dimensionally constant for only 24 h (29) . Disinfection was performed with spraying ready-made commercial disinfectant material: AHD 2000 (Alcohol-based disinfectant).It was used because alcohols are widely used by dentists (30) .…”
Section: Discussionmentioning
confidence: 85%